OPINIONS OF SENIOR SCHOOLCHILDREN ON DRUGS IN THE INTERNET: RESULTS OF A PILOT RESEARCH - A. A. Glukhova; A. A. Iudin; D. A. Shpilev (Russian Journal of Economics and Law)
Objective: to identify the level of engagement of schoolchildren in the process of distribution of narcotic drugs, psychotropic substances or their analogues via information and telecommunication networks of common use.Methods: the dialectical approach to cognition of social phenomena, allowing to analyze them in historical development and functioning in the context of the totality of objective and subjective factors that determined the choice of the following research methods: systematic-structural, comparative-legal, sociological.Results: the analysis was made of the involvement of schoolchildren in the process of distribution of narcotic drugs, psychotropic substances or their analogues through information-telecommunication network on the territory of the Russian Federation (by the example of Nizhny Novgorod region). The study revealed the existence of two groups of students: a group with psychological protection against harmful habits and a risk group. Each group has its own characteristics depending on sex, age, relationship to the use of narcotic drugs and psychotropic substances, social contacts of students, frequency of using the information-telecommunication networks of common use.Scientific novelty: for the first time on the basis of data obtained as a result of the socio-legal studies, the situation was reviewed concerning the distribution of narcotic drugs, psychotropic substances or their analogues via information and telecommunication networks of common use among secondary schools students. The social characteristics of a group with psychological protection against harmful habits and a risk group were identified. The proposal was made aimed at reducing the level of engagement of schoolchildren in the process of distribution of narcotic drugs, psychotropic substances or their analogues.Practical significance: the main provisions and conclusions of the article can be used in scientific and teaching activities in addressing issues related to combating illicit trafficking of narcotic drugs, psychotropic substances or their analogues.